Zaupanje med interesom in moralo - Iglič, Hajdeja (Teorija in praksa, 2012)
Trust is very important for the working of economic markets because it promotes economic transactions. Trust in economic relations cannot be established in a society where people routinely behave in an opportunistic way, which in the long term undermines economic growth. In order to understand the dynamics of the production of trust in a society with initially low levels of social trust, we distinguish between two different types of trust: predictive trust which builds on a specific constellation of interests, and altruistic trust which implies universalistic morality. We illustrate the theoretical argument with the help of historical cases from the early modern period of the development of a market society. We conclude the article by discussing the possibilities for the transition from a low to high trust equilibrium society, with reference to the two types of trust.
Keywords: Economic sociology; Ekonomska sociologija; Trust; Zaupanje; Exchange; Menjava; Družbena omrežja; Social networks; moralne norme